Habilidades profesionales e inserción laboral en los egresados de universidad nacional de la amazonía peruana filial Requena 2022 - Pasquel Huaymacari, Martin Antony (2023)
The purpose of this thesis was to determine the relationship between professional skills and job placement in graduates of the National University of the Peruvian Amazon, Requena branch. This was a descriptive-correlational investigation with a non-experimental design. 80 students participated in the data collection, for which the survey was used as a technique and the questionnaire as a tool. Coming to the conclusion that the professional skills in the professional graduates of the UNAP maintain a regular, limiting behavior to carry out group work, disinterest in continuous training, difficulty in communicating and minimal creative capacity, which makes it difficult to work efficiently in their job. On the other hand, the labor insertion in the graduated professionals is maintained at a medium level, this is due to the fact that there are difficulties in labor intermediation since there is minimal promotion of the same, in turn the labor situation is not entirely satisfactory for the employee. Finally, it can be deduced that there is a relationship between the variables, contrasted by a coefficient of 0.764.